On gas and hydraulic tightness of accelerating sections - Zhiglo, V.F. (Вопросы атомной науки и техники, 2021)
A technique for calculating the required impenetrability of brazing linac accelerating sections cooled by water and for control of their hydraulic tightness based on the total helium leakage rate is given. Three types of cooling systems: a water stream in tubes soldered on the outer surface of the sections, a water stream along the outer surface and along the internal cooling channels in sections are considered. It is shown that the contact of accelerating sections surface with cooling water requires increasing the tightness of their soldering at least by 66 times. As an example, requirements for hydraulic and air tightness of accelerating sections for the developed accelerator LU-10 NSC KIPT are given.